MENILAI PERAN KEPEMIMPINAN KYAI DALAM PENGEMBANGAN SANTRI - Muhammad Mujtabarrizza; Musyarafah Musyarafah (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2023)
Kyai's leadership role becomes a benchmark in providing a significant influence on the development of santri in all respects. The direction of implementing the development of santri lies in how unique the role carried by the Kyai is. Because in transformational leadership, the role is at the core of every pattern of measurable and structured development of students. The aim of the research is to assess the leadership role of the Kyai in developing students in each field of knowledge as a control in responding to moral conflicts. The research method is qualitative with a library research approach. The results of the study show that there are three roles in the Kyai's leadership in the development of santri, which include the interpersonal role, the decision role, and the information role.